2011
DOI: 10.1103/physrevb.83.100513
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic phase diagram and superconducting fluctuations of single-crystalline SmFeAsO0.85F0.15

Abstract: We report on the specific heat determination of the anisotropic phase diagram of single crystals of optimally doped SmFeAsO 1-x F x . In zero-field, we find a clear cusp-like anomaly in C/T with ΔC/T c = 24 mJ/molK 2 at T c = 49.5 K. In magnetic fields along the c-axis, pronounced superconducting fluctuations induce broadening and suppression of the specific heat anomaly which can be described using three-dimensional lowestLandau-level scaling with an upper critical field slope of -3.5 T/K and an anisotropy of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 49 publications
7
55
2
Order By: Relevance
“…For all compounds of iron based superconductors, the anisotropy ratio γ at T c (0) is in the range 2 to 5, similar to our finding in BaK122, with Ca 10 (Pt 3 As 8 )(( Fe 1−x Pt x ) 2 As 2 ) 5 with x = 0.09 [77], SmFeAsO 0.85 F 0.15 [78] and LaFe 0.92 Co 0.08 AsO [79] being exceptions, with γ ≈ 7 to 8.…”
Section: Doping Evolution Of the Anisotropy Parameter γsupporting
confidence: 70%
“…For all compounds of iron based superconductors, the anisotropy ratio γ at T c (0) is in the range 2 to 5, similar to our finding in BaK122, with Ca 10 (Pt 3 As 8 )(( Fe 1−x Pt x ) 2 As 2 ) 5 with x = 0.09 [77], SmFeAsO 0.85 F 0.15 [78] and LaFe 0.92 Co 0.08 AsO [79] being exceptions, with γ ≈ 7 to 8.…”
Section: Doping Evolution Of the Anisotropy Parameter γsupporting
confidence: 70%
“…3a. Subtraction of the normal state background as described in detail in Welp et al 16 yields the superconducting specific heat near the transition as shown in Fig. 3b for the pristine and B F ¼ 4 T irradiated sample no.…”
Section: Resultsmentioning
confidence: 99%
“…BaFe 2 (As 1-x P x ) 2 , and in strongly scattering charge doped compounds. A notable exception from this scaling is Sm-1111 [17] for which the specific heat anomaly is roughly a factor of 10 too small as compared to the BNC-scaling.…”
mentioning
confidence: 94%